Úloha T-regulačních lymfocytů v patogenezi předčasného porodu - Hrbáčková, H; Koucký, M; Malíčková, K; Černý, A; Gáborová, E; Kopřivová, H; Hinďoš, M (Ceska gynekologie, 2017)
OBJECTIVE: To describe the role of T-regulatory lymphocytes in pathogenesis of preterm delivery. SETTING: Department of Obstetrics and Gynecology, General University Hospital and 1st Medical Faculty, Charles University, Prague. METHOD: T-regulatory lymphocytes modulate the immune system, secure the tolerance to own antigens and prevent autoimmune disease. During pregnancy is maternal immunity in contact with the semi-allogeneic fetus due to the fetomaternal crosstalk. It seems that maternal immunity and T-regulatory lymphocytes have an effect on premature birth and other pregnancy pathologies. According to the latest data, their role in the immunomodulation of pregnant women seems to be very significant, although we still do not understand many mechanisms.
Keywords: premature birth immunomodulation in pregancy.; T-Lymphocytes, Regulatory; Infant, Newborn; plod; Premature Birth; ženské pohlaví; novorozenec; předčasný porod; imunomodulace; regulační T-lymfocyty; Fetus; Humans; Female; Pregnancy; těhotenství; T-regulatory cells; lidé; Immunomodulation